MALLing YOUR WAY TO PERFECT PRONUNCIATION: A SYSTEMATIC REVIEW (2020-2024) - Nadrotul Muslimah; Nafan Tarihoran (INJOSEDU: International Journal of Social and Education, 2025)
In industrial technology 4.0, Mobile Assisted Language Learning (MALL) has positively impacted the teaching and learning process, particularly in pronunciation skills. Thus, this systematic review identifies the trends of technological innovations, and pedagogical approaches of Mobile Assisted Language Learning MALL in teaching pronunciation from a diverse range of studies and examines the effectiveness of Mobile Assisted Language Learning (MALL) in teaching pronunciation. Using three databases, Mendeley, ScienceDirect, and Eric, 5 articles were extracted out of 399, from 2020-2024, with exclusion and inclusion criteria considered. The analysis highlights the benefits of Mobile Assisted Language Learning MALL, such as increased accessibility, personalized feedback, and interactive learning experiences. Next, the finding implies that Mobile Assisted Language Learning MALL teaching pronunciation can positively impact students' pronunciation skills. Besides, it also influences students' interest in the teaching-learning process, which tends to students' creativity, since it can save time, energy, and money.